1995
DOI: 10.1029/95ja02495
|View full text |Cite
|
Sign up to set email alerts
|

Sudden impulses at subauroral latitudes: Response for northward interplanetary magnetic field

Abstract: The response of subauroral H component magnetograms at the time of passage of interplanetary shocks under northward interplanetary magnetic field (IMF) conditions is used to examine the behavior of the magnetosphere when it is suddenly compressed. At subauroral latitudes, near 55 ø or L = 3, the response has some similarities and some important differences from the low-latitude response. The first effect is a preliminary impulse which appears to be due to the Hall current driven in the ionosphere by the arriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 19 publications
7
72
4
Order By: Relevance
“…Recently, in a statistical study, Francia et al (1999) analyzed some events occurring during northward IMF conditions and showed that the geomagnetic field horizontal component H at a low-latitude station (L'Aquila) responds very well to the SW pressure variations on a time scale of few minutes. The amplitude of the geomagnetic response was found to be linearly related to the change in the square root of the SW dynamic pressure, and its average amplitude (∼13 nT/(nPa) 1/2 ) is comparable with the values found by Russell et al (1994) and Russell and Ginskey (1995) at low and subauroral latitudes in the analysis of the sudden impulse (SI) response to the passage of interplanetary shocks. Moreover, the amplitude of the response was found to depend on local time, with greater values around local noon and midnight and a pronounced minimum during the local morning.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Recently, in a statistical study, Francia et al (1999) analyzed some events occurring during northward IMF conditions and showed that the geomagnetic field horizontal component H at a low-latitude station (L'Aquila) responds very well to the SW pressure variations on a time scale of few minutes. The amplitude of the geomagnetic response was found to be linearly related to the change in the square root of the SW dynamic pressure, and its average amplitude (∼13 nT/(nPa) 1/2 ) is comparable with the values found by Russell et al (1994) and Russell and Ginskey (1995) at low and subauroral latitudes in the analysis of the sudden impulse (SI) response to the passage of interplanetary shocks. Moreover, the amplitude of the response was found to depend on local time, with greater values around local noon and midnight and a pronounced minimum during the local morning.…”
Section: Introductionsupporting
confidence: 63%
“…Moreover, the amplitude of the response was found to depend on local time, with greater values around local noon and midnight and a pronounced minimum during the local morning. A similar local time dependence, although characterized by a greater excursion between maximum and minimum values, was also found by Russell and Ginskey (1995) in the analysis of SIs at subauroral latitudes (near 55 • ).…”
Section: Introductionmentioning
confidence: 59%
“…We found that the amplitude of the geomagnetic response R to the SW pressure increases is of the same order as at lower [Russell et al, 1994] and subauroral latitudes [Russell and Ginskey, 1995]; its local time dependence is different than at lower latitudes while is very similar to that observed at subauroral latitudes: indeed, it is characterized by a strongly depressed response in the local morning with respect to afternoon and night sectors and by a clear maximum at local noon. This result suggests that, also at our latitudes, the contribution of high-latitude ionospheric currents is important [Araki, 1994;Russell and Ginskey, 1995;Tsunomura, 1998].…”
Section: Discussionmentioning
confidence: 55%
“…We found that the amplitude of the geomagnetic response R to the SW pressure increases is of the same order as at lower [Russell et al, 1994] and subauroral latitudes [Russell and Ginskey, 1995]; its local time dependence is different than at lower latitudes while is very similar to that observed at subauroral latitudes: indeed, it is characterized by a strongly depressed response in the local morning with respect to afternoon and night sectors and by a clear maximum at local noon. This result suggests that, also at our latitudes, the contribution of high-latitude ionospheric currents is important [Araki, 1994;Russell and Ginskey, 1995;Tsunomura, 1998]. In this sense it is interesting to recall that the same diurnal variation was also found at our In this sense it is interesting to remark that variations in plasmaspheric density and in plasmapause radius during magnetic storms have been investigated at high latitudes and midlatitudes using whistler measurements; it was found that, after the depletion during the storm, the plasmasphere refilling from the ionosphere takes place with a characteristic time of the order of 8 days at L=4 [Park, 1974] …”
Section: Discussionmentioning
confidence: 55%
“…[59] A further consequence of the HPS-HCS passage is a sudden impulse in the northward magnetic field recorded by subauroral dayside ground magnetometers [e.g., Le et al, 1993;Russell and Ginskey, 1995], an ionospheric current response to the HPS density increase. The International Monitor for Auroral Geomagnetic Effects (IMAGE) magnetometer chain, located postnoon between 1400 and 1500 MLT in Scandinavia, saw a positive change of nearly 100 nT, peaking near 1220 UT and then decaying (not shown).…”
Section: Hydrodynamic and Magnetohydrodynamic Coupling To The Magnetomentioning
confidence: 99%